Cause Analysis and Countermeasures of Pupil’s Studying Weariness in Yemen - Alhashedi, Sena; Sun Xiao Jun,; Abdullah ALfalahi, (IJRDO- Journal of Educational Research, 2019)
As the fundamental of a country, education occupies an important position in the development of a country. Primary education is an important component of the national education; however, studying weariness among pupils in primary school is the main factor affecting the development of education. It is therefore essential to detect studying weariness among students in primary school and solve them. As they grow older, pupils are having gradually strengthened self-awareness while at the same time they are facing mounting pressure of study. Hence it is imperative to find out the countermeasures of studying weariness among them. In this thesis, I carried out the research by using literature method, interviewing method and questionnaire method. Firstly, the concept of studying weariness is defined. Secondly, Questionnaires and interviews on studying weariness at a certain primary school are carried out and analyzed. Thirdly, the cause of studying weariness among pupils in primary school is analyzed. Lastly, in order to solve the problem of studying weariness among pupils in primary school, the thesis proposed the following countermeasures and suggestions, the government should strengthen supervision and management culture; school teachers to enhance and strengthen the hardware facilities of the school, attention to student mental health; teachers to upgrade their professional quality, master scientific teaching methods, the establishment of equal and harmonious relationship between teachers; parents will educate their children the proper way to create a happy family atmosphere, and actively involved in school education; students themselves to recognize the importance of learning and study hard. The countermeasures and suggestions in this study are proposed by me on the basis of personal interviews, which are designed to provide true and reliable basis to solve studying weariness among students. These countermeasures and suggestions are researchers in this survey through personal interviews and on the basis proposed, designed to provide true and reliable basis for solving problems students’ weariness. This paper comes up with relevant intervention strategies on psychological features of vocational high school students’ school weariness in combination with the theories of psychology, especially affective strategies commonly used in applied educational psychology, to make psychological counseling for elementary students’ school weariness, which allows the teachers of vocational high school to solve the psychological problems of students’ school weariness during their educational practice in a more scientific and effective way under the guidance of theory.